Management of Natural-Anthropogenic Complexes of Rural Territories in the Context of the Post-non-Classical Type of Scientific Rationality - NARDIN, Dmitry Sergeevich; NARDINA, Svetlana Aleksandrovna (Journal of Environmental Management and Tourism; Vol 12 No 5 (2021): JEMT Volume XII Issue 5(53) Fall 2021, 2021)
The purpose of this study is to analyze the problem of management of natural-anthropogenic complexes of rural territories in the context of the post-non-classical type of scientific rationality at the philosophical and methodological levels. The problem of management of natural-anthropogenic complexes is considered and analyzed in the article at the philosophical level in the context of the humanistic interpretation of philosophical constructivism. At the methodological level, the management of natural-anthropogenic complexes of rural territories is considered in the basic paradigm “subject – metasubject”, in which a natural-anthropogenic complex is presented in the form of a self-developing environment, an integrated study of which is possible only using an interdisciplinary approach.